Implementasi Arduino dan ESP32 CAM untuk Smart Home - Wicaksono, Mochamad Fajar; Rahmatya, Myrna Dwi (Jurnal Teknologi dan Informasi (JATI), 2020)
This study describes the implementation of a smart home by utilizing Arduino and ESP32 CAM with IoT technology. The purpose of this research is to make a device to control home appliances and monitor home security. The method used in this study is an experimental method. In this study, Arduino is used as the main brain of the system where Arduino will read temperature sensor, PIR sensor, LDR and control whether or not the lamp, fan and PIR sensors are active. Sensor data will continue to be sent to the server by the Arduino through the ESP32 CAM module. This tool can also send photos automatically when any movement is detected. Photos taken automatically will be sent to homeowners via the Line application. The process of taking photos, activating lights, fans and PIR sensors can also be done manually via the web interface by the user. Users can also view data from Arduino sent sensors via the web interface that has been provided. From the results of testing this tool has been running well where all sensor data is sent and can be stored in a database, manual activation and deactivation can be done, the captured image is sent to the user's Line application with percentage 100%.